Dampak Program Keluarga Harapan (PKH) terhadap Peningkatan Kesejahteraan Keluarga Miskin di Kelurahan Kerasaan I Kecamatan Pematang Bandar Kabupaten Simalungun - Listy Julfani; Ilham Mirzaya Putra (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The Family Hope Program (PKH) is a conditional cash transfer program for low-income families. The requirement is to be actively involved in education and health. The Family Hope Program in Indonesia was implemented in 2007 to alleviate poverty and prosper low-income families. This research and journal article aims to determine the impact of PKH on family welfare and see if there is a reduction in the poverty rate after the government realizes the Family Hope Program. This study uses a qualitative method with a descriptive approach. Collecting research data in the form of observations, interviews and documentation with PKH Facilitators and PKH beneficiary families (KPM) Kerasaan I Village, Pematang Bandar District, Simalungun Regency. The results of the study show that the impact of PKH on beneficiary families, including the cash provided, can meet family consumption or needs and help the economy of PKH beneficiary families. Program implementation can reduce poverty in Kerasaan I Village. The percentage of poor people in September 2021 was 0.14% and decreased in March 2022 to 0.02%. The limitation of the research is the impact of PKH on family welfare and wanting to examine whether there is a decrease in the percentage of poverty in Pematang Bandar District or more precisely in the Kerasaan I Village. The practical implication of this research is to provide information to the government that PKH can increase the welfare of low-income families. Its social meaning is to provide an overview to the government and the community that the implementation of social assistance programs, one of which is the Family Hope Program, can reduce the poverty rate in Kerasaan I Village, Pematang Bandar District. The purity of this research is supported by the Kerasaan I Kelurahan PKH Facilitator who helps the community get out of poverty through a family capacity building meeting program (P2K2) which is held every month. Keywords: Impact, Family Hope Program, Family Welfare. Kerasaan I Village